The Relationship Of Mother's Level Of Knowledge, Employment And Particular History With The Giving Of Colostrum To Newborn Babies At The Manda Clinic In 2024 - Sinaga, Mariana; Tampubolon, Emelia Apriani (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2024)
Background:Breastfeeding is the process of giving breast milk (ASI) to a newborn baby. Breastfeeding is beneficial for the growth and development of babies, especially giving yellowish first breast milk (colostrum).Purpose: The aim of the research was to determine the relationship between mother's knowledge, employment and birth history with the provision of colostrum to newborns. Method:This type of research is a quantitative description with a cross sectional approach. The research population was all 30 postpartum mothers at the Manda Clinic. The sample uses a total sampling technique.Result: showed that the majority had 13 people (43.3%) who had insufficient knowledge, 12 people (40%) had their respective occupations as non-employed/domestic workers and self-employed workers, and 14 people (46.7%) had a history of multiparous childbirth.Conclusion: From the results of the chi-square test, it was found that there was a relationship between knowledge and giving colostrum with a p-value of 0.026, there was a relationship between work and giving colostrum with a p-value of 0.021, there was a relationship between birth history and giving colostrum with a p-value of 0.028. Postpartum mothers are expected to provide colostrum to newborn babies which is beneficial for the baby's growth and development